2010
DOI: 10.3109/02656730903341332
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation-based thermal treatment planning for catheter-based ultrasound hyperthermia

Abstract: A patient-specific optimisation-based hyperthermia treatment planning program for catheter-based ultrasound technology was developed for a priori evaluation of proposed applicator implant strategies and determination of initial applied power settings. The interstitial and endocavity heating applicators, designed for delivering 3-D controllable hyperthermia within High Dose Rate (HDR) brachytherapy implants, consist of linear and sectored arrays of ultrasound transducers with variable power control in both leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 60 publications
0
54
0
Order By: Relevance
“…Based on the positions of implanted applicators as determined by imaging, forward and/or inverse treatment planning tools may be used to determine appropriate power levels for adequate thermal coverage of the target, as has been implemented for interstitial ultrasound hyperthermia procedures. 69 CT and ultrasound are the most commonly used imaging modalities for guiding percutaneous tumor ablation. 70 For parallel implants, the use of surface templates (as used for currently available RF and MW ablation systems) can augment imaging data to assess applicator positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the positions of implanted applicators as determined by imaging, forward and/or inverse treatment planning tools may be used to determine appropriate power levels for adequate thermal coverage of the target, as has been implemented for interstitial ultrasound hyperthermia procedures. 69 CT and ultrasound are the most commonly used imaging modalities for guiding percutaneous tumor ablation. 70 For parallel implants, the use of surface templates (as used for currently available RF and MW ablation systems) can augment imaging data to assess applicator positioning.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,8 Treatment planning based on both specific absorption rate (SAR) and temperature-based optimization has been used to provide better targeted heating in various sites. [9][10][11] Treatment planning that enhances the ability to focus heat at the bladder has also been reported. For example, van Dijk et al 12 showed increased bladder SAR using treatment planning to optimize the SAR distribution in a selected two-dimensional plane.…”
Section: Introductionmentioning
confidence: 99%
“…Since, on the first steps of cryoablation, an open surgery was required due to large probe sizes and the risk of bleeding, RF ablation has gained wide acceptance as a minimally invasive technique and becomes the most widely used hyperthermia technique to treat liver cancer, see [2][3][4] and the references therein. Nowadays the cryogenic treatment has modern catheters that can be 2 mm maximum diameter with 90 cm flexible length and then it also belongs to the more recent area of study of the thermal therapies as well as the application of imaging, ultrasound, and laser modalities among others [5][6][7][8][9]. Although our data may be specific to RF ablation in the liver, the continuum models are probably valid for all thermal ablation energy sources and for other organs which are close to vessels.…”
Section: Introductionmentioning
confidence: 55%